Dél-Dunántúl oktatási és kulturális helyzetének vizsgálata - Szűcs, Krisztián (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Within the framework of the European Union's Social Renewal Operational Programme "TÁMOP" in which the South Transdanubian development opportunities are being researched, we placed special emphasis on the educational and cultural situation which essentially forms the basics of the quality of the human resource. The importance of it is clear as a developing economy can only emerge if professional human resource that can supply and operate the demand is available in the region. The development of an educational system that meets the needs of the economic system has been failed so far. Some examples can prove this statement: the lack of experts had been the reason for new industries not to come to the region. The examination of the educational and cultural situation is also important because the region centres have had long history of education which can be an economic potential as they attract students from other regions.